2013
DOI: 10.1039/c3dt50933h
|View full text |Cite
|
Sign up to set email alerts
|

Reversible hydrogen desorption from LiBH4 catalyzed by graphene supported Pt nanoparticles

Abstract: The thermally induced de-/rehydrogenation performance of the graphene supported Pt nanoparticles (Pt/G) doped LiBH4 was greatly improved even at very low catalyst content due to a synergetic effect of Pt addition and nanoconfinement in graphene. For the 5 wt% Pt/G doped LiBH4 sample, the onset hydrogen desorption temperature is about 140 °C lower than that of the pure LiBH4. With increasing loading of the Pt/G catalysts in LiBH4 samples, the onset dehydrogenation temperature and the two main desorption peaks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The addition of several TM-compounds has indeed resulted in improved hydrogen storage properties of stable borohydrides and related composites, including decrease in Tdec [35,41], in some cases remarkably by as much as 200 °C [36]. Enhancement of the desorption and absorption reactions kinetics [26,42], improved hydrogen purity, reversibility [37] and borohydride synthesis from the decomposition products [39] has also been documented.…”
Section: Introductionmentioning
confidence: 98%
“…The addition of several TM-compounds has indeed resulted in improved hydrogen storage properties of stable borohydrides and related composites, including decrease in Tdec [35,41], in some cases remarkably by as much as 200 °C [36]. Enhancement of the desorption and absorption reactions kinetics [26,42], improved hydrogen purity, reversibility [37] and borohydride synthesis from the decomposition products [39] has also been documented.…”
Section: Introductionmentioning
confidence: 98%
“…25 The addition of functional graphene to LiBH 4 could result in a high hydrogen storage capacity, rapid kinetics, and excellent reversibility. Xu et al 26,27 reported that precious metal (Pt and Pd) nanoparticles anchored onto graphene sheets could greatly improve the hydrogen desorption behavior and uptake reversibility of LiBH 4 . The artful combination of catalysis and nanoconnement has become a promising way to improve the dehydrogenation and rehydrogenation performance of LiBH 4 .…”
Section: 24mentioning
confidence: 99%
“…MS results demonstrate that the gas released from all samples is pure H 2 without B 2 H 6 or NH 3 impurity. Furthermore, the onset dehydrogenation temperature of NbCl 5 /h-BN co-doped LiBH 4 is reduced to 180 C, which is 100 C lower than that of the ball milled LiBH 4 [31,32]. Also, the major desorption peak temperatures of LiBH 4 -0.01NbCl 5 -0.3BN sample is 377 C, which is much lower than the other three samples.…”
Section: Resultsmentioning
confidence: 53%